Area and Bandwidth Enhancement of an n+/p-Well Dot Avalanche Photodiode in 0.35 μm CMOS Technology - Seyed Saman Kohneh Poushi; Bernhard Goll; Kerstin Schneider-Hornstein; Michael Hofbauer; Horst Zimmermann (Sensors, 2023)
This paper presents a CMOS-integrated dot avalanche photodiode (dot-APD) that features a small central n+/p-well hemispherical cathode/p-well structure circularly surrounded by an anode ring. The dot-APD enables wide hemispherical depletion, charge collection from a large volume, and a small multiplication region. These features result in a large light-sensitive area, high responsivity and bandwidth, and exceptionally low junction capacitance. The active area can be further expanded using a multi-dot structure, which is an array of several cathode/p-well dots with a shared anode. Experimental results show that a 5 × 5 multi-dot APD with an active area of 70 μm × 70 μm achieves a bandwidth of 1.8 GHz, a responsivity of 9.7 A/W, and a capacitance of 27 fF. The structure of the multi-dot APD allows for the design of APDs in various sizes that offer high bandwidth and responsivity as an optical detector for various applications while still maintaining a small capacitance.